PENGUATAN KEBERLANGSUNGAN USAHA PERAJIN GAMELAN GOMBLOH MELALUI INOVASI DIGITAL DI BIBIS BANGUNJIWO YOGYAKARTA - Finanda, Septi Asri; Utama, Satria; Nurhayati, Emmy (Institut Seni Indonesia Surakarta, 2025)
Various aspects of human life, including the local economy, have been significantly influenced by advancements in digital technology. The Gamelan asrtisans of Gombloh in Bibis, Bangunjiwo, Bantul, Yogyakarta, continue to face challenges in marketing and managing their businesses. This community service program implements digital innovation in financial management and marketing of gamelan products to help sustain these enterprises. The technology-based activities include the application of online marketing strategies through e-commerce platforms and social media, as well as the creation of effective financial and production management systems. Additionally, training sessions were conducted to enhace the knowledge and skills of gamelan artisan ini digital marketing. Explores issues and creative ideas through by Focus Group Discussion (FDG). The results of the program indicate that the implementation of digital technology has improved the efficiency of managing their businesses. The local community has also been strengthened by the collaboration among gamelan artisans fostered during this program. The positive response from the community towards gamelan Gombloh highlights the importance of integrating tradition with contemporary practices. Overall, this program demonstrates that digital innovation is a crucial strategic step for sustaining the Gamelan artisans’ enterprises. By leveraging technology, they can preserve their businesses while also safeguarding Indonesia’s cultural heritage for future generations.